THE EFFECT OF TAX KNOWLEDGE ON WILLINGNESS TO PAY TAXES WITH AWARENESS OF PAYING TAXES AS A MODERATING VARIABLE - Vina Alviani; Analisa Analisa; Yusri Yusri; Nadya Novianty (Klabat Accounting Review, 2023)
Taxes play an important role in contribututing to state revenue, more than 80% of state revenue currently comes from taxes. This research aims to see the effect of tax knowledge on the willingness to pay taxes with awareness of paying taxes as a moderating variable. This type of research is quantitative research with a questionnaire as an instrument for collecting data. The population in this study are individual taxpayers of PPh Article 21 who live in the city of Banjarmasin. The sampling technique used was random sampling with the Slovin formula so that a sample of 100 was obtained. The data analysis technique used simple linear regression analysis and moderated regression analysis test. The results of this study indicate that tax knowledge has a significant effect on the willingness to pay taxes. Awareness of paying taxes strengthens the relationship between tax knowledge and willingness to pay taxes as a moderating variable. Keywords: Awareness of paying taxes, Knowledge of taxation, PPh 21, Willingness to pay taxes Pajak berperan penting dalam kontribusi penerimaan negara, lebih dari 80% penerimaan negara saat ini bersumber dari pajak. Penelitian ini bertujuan untuk melihat pengaruh pengetahuan perpajakan terhadap kemauan membayar pajak dengan kesadaran membayar pajak sebagai variabel moderasi. Jenis penelitian ini adalah penelitian kuantitatif dengan kuesioner sebagai instrument untuk mengumpulkan data. Populasi dalam penelitian ini adalah wajib pajak orang pribadi PPh pasal 21 yang berdomisili di kota Banjarmasin. Teknik pengambilan sampel yang digunakan yaitu random sampling dengan rumus slovin sehingga diperoleh sampel sebanyak 100. Teknik analisis data menggunakan analisis regresi linier sederhana dan uji moderated regression analysis. Hasil penelitian ini menunjukkan bahwa pengetahuan perpajakan berpengaruh signifikan terhadap kemauan membayar pajak. Kesadaran membayar pajak memperkuat hubungan pengetahuan perpajakan terhadap kemauan membayar pajak sebagai variabel moderasi. Kata kunci: Kesadaran Membayar Pajak, Pengetahuan Perpajakan, PPh 21, Kemauan membayar pajak